Examination and Comparison of Nuclear Energy with other Available Energy Sources for Electricity Production in Turkey - Serteller, N. Fusun Oyman (International Journal of Humanities and Social Science Research, 2018)
This paper presents the nuclear options for Turkey’s energy future while comparing the other available energy sources. Firstly, importance of sustainable energy sources and policies are discussed. Should existing energy policies which formed mostly by importing energy (natural gas) from the neighbors’ countries continue or should find different alternatives such as local energy sources (wind and solar energy) and nuclear energy be evaluated. Then, the potential of the local renewable sources convenient for Turkey, such as wind and solar are investigated and compare with the nuclear energy. The advantages and disadvantages of nuclear energy usage, as well as the place of nuclear energy in electricity production in the world are scrutinized. It is clear that the usefulness of nuclear energy and nuclear power plants depend heavily upon the progress in technical developments. Improving technology on operation systems and waste problems of them brings more secure and more environment friendly power plants. Finally, our current energy consumption and energy need in short and medium term (+50) conducted for the evaluation of nuclear power plants are discussed.